Cutaneous tuberculosis in Niger: a 9-year retrospective study - Laouali Salissou; Eric Adehossi; Sani Maman Laouali; Saidou Mamadou; Hassan Nouhou (Our Dermatology Online, 2015)
Introduction: Cutaneous tuberculosis is a skin infection due to the Mycobacterium tuberculosis and rarely due to Mycobacterium bovis or Mycobacterium africanum. The disease is difficult to diagnose, given the fact that the skin is seldom a location for tuberculosis. The aim of this study is to determine the epidemiological, clinical and therapeutic profile of the disease in Niger. Materials and Methods: This is a retrospective study over a period of 9 years in the Department of Dermatology and Venereology at the National Hospital of Niamey. The study included all cases of cutaneous tuberculosis that were clinically diagnosed and confirmed or not by some conventional complementary examinations. Results: Over a period of nine years, 49 cases of cutaneous tuberculosis were diagnosed, which represents 0.34% of the total 14376 dermatological consultations in the dermatological unit. Patients of both sexes were affected, but the majority were male with 69% or a sex ratio M/F of 2.26. The patients ranged in age from 6 to over 60 years. The mean age was 34.67 years. Patients between 31 and 40 years were the most affected at 34.69%. A personal or family history of tuberculosis was noted in 8.16% of the cases. Scrofuloderma is the most frequent form of the disease (93.87% of the cases). The average course of the disease before consultation was 30.28 months. The tuberculin skin test was positive in 83.67% of the cases. The TB smear test was positive in only 6% of the cases. The hyperleukocytosis, which was mostly lymphocytic, was noted in 21.62% of the cases. Radiological evaluation was normal in 91.83% of the cases. All patients responded well in 100% of the cases with a treatment period ranging from 6 to 9 months. No clinical and/or biological treatment-related side effects were observed. Conclusion: Cutaneous tuberculosis is still a common infection in third world countries where it affects both sexes. The scrofuloderma is the most observed form in our study. A TB test-based treatment is often a good solution in the face of an array of clinical and epidemiological evidence. Systematic vaccination after birth would drastically reduce all forms of tuberculosis.